The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1161/jaha.117.006431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hemodialysis on Procedural Outcomes of Percutaneous Coronary Intervention for Chronic Total Occlusion: Insights From the Japanese Multicenter Registry

Abstract: BackgroundAmong patients treated with percutaneous coronary intervention for chronic total occlusion (CTO‐PCI), patients on long‐term hemodialysis are at significantly high risk for cardiovascular mortality and morbidity. However, clinical or angiographic predictors that might aid in better patient selection remain unclear. We aimed to assess the acute impact of hemodialysis in patients who underwent CTO‐PCI.Methods and ResultsThe Retrograde Summit registry is a multicenter, prospective registry of patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…There are several possible explanations for these findings, including younger age patients, less STEMI presentation, less cardiogenic shock and mostly of the PCI procedure were planned. Our study supported the previous studies that contemporary PCI is feasible and safe in appropriated selected patients with higher technical success and acceptable complication rates, even though they require more complex PCI procedure 27 . However, it needs to be emphasize that the 1‐year all‐cause mortality in these patients was still high after adjustment for other risk factors which mostly was driven by CV death or sudden death (56.5%) and additional unplanned revascularization.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…There are several possible explanations for these findings, including younger age patients, less STEMI presentation, less cardiogenic shock and mostly of the PCI procedure were planned. Our study supported the previous studies that contemporary PCI is feasible and safe in appropriated selected patients with higher technical success and acceptable complication rates, even though they require more complex PCI procedure 27 . However, it needs to be emphasize that the 1‐year all‐cause mortality in these patients was still high after adjustment for other risk factors which mostly was driven by CV death or sudden death (56.5%) and additional unplanned revascularization.…”
Section: Discussionsupporting
confidence: 87%
“…Impaired renal function was the study factor of interest and was classified into six CKD groups: stage I (GFR ≥ 90), stage II (GFR 60−89), stage III (GFR 30−59), stage IV, 15–29 stage V (GFR < 15 ml/min/1.73 m 2 ) without dialysis, and stage V with dialysis. The estimated GFR (ml/min/1.73 m 2 ) was calculated based on the CKD epidemiology collaboration (CKD‐EPI) equations 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several important prognostic factors, such as reduced left ventricular ejection fraction [11], anemia [12], and hemodialysis [13], have been identified, albeit the prognostic benefit of successful CTO-PCI does not differ according to the presence or absence of these prognostic factors. These factors are helpful in identifying high-risk patients who require close clinical follow-up and/or aggressive risk factor modification.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis is generally thought to be one of the major risk factors for cardiovascular events after percutaneous coronary intervention (PCI) [5][6][7]. Previous studies have revealed poor clinical outcomes among hemodialysis patients after PCI in comparison with non-hemodialysis patients in long-term clinical follow-up [8][9][10][11]. Diffuse and severe calcifications are typical lesion characteristics after PCI in hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%